PROTOTYPE SISTEM KENAIKAN PANGKAT APARATUR SIPIL NEGARA DI PEMERINTAH KABUPATEN BOALEMO - Hadi Pratomo; Alter Lasarudin; Frangky Tupamahu; Wahyudin Hasyim (LPPM Universitas Muhammadiyah Gorontalo, 2026)
This study aims to design a prototype of a web-based Civil Servant Promotion System for the Government of Boalemo Regency using a User Interface and User Experience (UI/UX) approach. The existing promotion administration process still relies on semi-manual procedures, resulting in delays in document verification, difficulties in monitoring proposal status, limited transparency, and inefficiencies in personnel data management. The research employed a Prototyping method using Figma involving three main actors, namely OPD Administrator, BKPSDM Administrator, and BPKPD Administrator. The prototype was developed to support promotion submission, administrative verification, document management, and monitoring of promotion status through an integrated digital workflow. System feasibility evaluation was conducted using the System Usability Scale (SUS) involving 15 respondents. The evaluation results showed that the prototype obtained an average score of 90.5 on a scale of 0–100, which falls into the Excellent category, indicating a very high level of usability and user acceptance. Therefore, the proposed prototype is considered feasible as a reference for the development of an integrated personnel information system that can improve efficiency, transparency, and service quality in the civil servant promotion process within the Government of Boalemo Regency